A Case Study of Relationship between CO2 Emissions, Growth, Energy and Electricity Consumptions in Morocco - Wafa Kerfal; Aicha El Alaoui (European Scientific Journal, ESJ, 2024)
Given the uncontrolled increase in environmental pollution and degradation of environmental quality worldwide, the environmental impact of economic growth has become a major focus in recent decades the most important question is: How does economic growth effect environmental quality? This study addressed this issue, examining the nature of the long-run relationship between economic growth per capita and pollutant emissions in Morocco. For this reason, the ARDL (Autoregressive Distributed Lag) modeling approach was used from 1990 to 2020. This approach mainly includes time series analysis and cointegration. The relationship tested introduces four variables: carbon dioxide (CO2), energy consumption per capita, electricity consumption per capita and GDP per capita. The main results indicate a long-term relationship between economic growth, energy consumption and CO2 emissions, indicating that a 1% increase in electricity consumption increases CO2 emissions by 0.36%. On the other hand, a 1% increase in GDP per capita increases CO2 emissions by 0.76%, and a 1% increase in energy consumption increases emissions by 2.06%. Thus, all variables show a significant effect.In conclusion, the strategy that Morocco needs to follow to solve our problems is to prioritize investment in research, development and artificial intelligence, while providing adequate training in energy-related fields.